GAMBARAN BODY MASS INDEX, RIWAYAT PENDIDIKAN, DAN KETURUNAN PASIEN HIPERTENSI PUSKESMAS SINTANG - hendra hendra (CHMK HEALTH JOURNAL, 2021)
Background: Hypertension is chronic increased of blood pressure ≥140/90 mmHg. Hypertension increasing stroke and myocardial infarction risks. This study aims to describe Body Mass Index, education level and family history in patient with hypertension in Sintang Public Health Center that related to patient’s treatment. Methods: Descriptive study of hypertension data in January 2019, that analysed with Microsoft Excel 2010. Results: A total 33 patients were involved in this study. The most Body Mass Index in patient were 18 persons(54,6%) been classified as overweight and obesity. For education level, as 24 patients (72,7%) were in elementary school. Patient that have family history of hypertension were only 10 persons (30,3%). Conclusion: The overweight, obesity and elementary school level are dominating in hypertension. Although, only 30,3 % patient with family history of hypertension. Further research can be done with cohort design. Keywords: Hypertension, BMI, education, familial